O manual pedagógico como ferramenta de inclusão: um olhar reflexivo sobre os paradigmas educacionais do núcleo de atendimento às pessoas com necessidades específicas do Instituto Federal de Alagoas - Campus Piranhas - Cunha, Taiza Lima da (2020)
The educational paradigms of an inclusive nature require a wide systematic, humanistic and epistemological reflection that aggregate the values of diversity, solidarity and holistic teaching as the basis of the national educational system. Education in its broad and freiriano context ratifies the mission of guaranteeing a pedagogical praxis based on the triad of education, work and citizenship, and which directs to guarantee the access, permanence and academic success of students with Specific Educational Needs (NEE), overturning stereotypes and physical, human and social barriers that hinder the realization of inclusion. This work had as fundamental objective the making of a Pedagogical Manual that corroborates the educational works developed by the Support Center for People with Specific Needs (NAPNE) of the Federal Institute of Alagoas (IFAL), Campus Piranhas. The construction of the referred Manual, under the paradigms of inclusive education, aims to provide pedagogical support in the context of attending students with NEE. It seeks to reflect on the role of NAPNE in this perspective of education for all and with everyone, together with the academic community, for the ratification of a school space consolidated in critical educational philosophy, having human diversity as the basis of the educational context. Thus, this work adopted the action research methodology and the participants were the NAPNE members of the IFAL Campus Piranhas. Questionnaires were used in diagnostic research and to evaluate the educational product. The evaluation highlighted that the Manual is a guiding instrument and of substantial importance for the visibility and enhancement of NAPNE, and that it reiterates the educational, human and social commitment of education as a mechanism for transforming excluding realities. The aforementioned Manual was accepted and well regarded for the propagation of an inclusion perspective as a priority within IFAL, being extremely important for the dissemination and valuation of inclusive paradigms.